"Preliminary results of hydrogen production from water vapor decomposition using DBD plasma in a PMCR reactor". (26th July 2019) - El-Shafie, Mostafa; Kambara, Shinji; Hayakawa, Yukio; Miura, Tomonori
Abstract: The water decomposition is considered one of the most attractive chemical processes for the production of hydrogen. The present work describes the preliminary results obtained in the experimental study of the water vapor dissociation into hydrogen and oxygen species using Dielectric-Barrier Discharge (DBD) plasma in a plate micro-channel reactor (PMCR). The water vapor molecules are injected without using carrier gas into the PMCR reactor at pressure of 100 kPa and temperature of 573 K. The applied high voltage of the plasma was within range of 14–18 kV and different steam flow rates have been analyzed within range of 100–200 ml/h. The product gases have been separated in ice trap which it was connected directly to the PMCR reactor to prevent the recombination of hydrogen and oxygen species. The concentration of the outlet species has been measured in a gas phase chromatography (GC) instrument. The PMCR reactor heating temperature effect on the water vapor decomposition has been analyzed. It was found that the water vapor is dissociated into their constituent molecular elements of hydrogen and oxygen gas using plasma. The maximum obtained mole fraction, hydrogen flow rate and conversion rate were 2.3%, 9.42 g/h, 42.51% respectively, at steam temperature of 573 K, pressure 100 kPa, PMCR heating temperature 403 K, steam flow rate of 200 ml/h and the plasma discharge high voltage of 18 kV. It was observed that the amount of evolved hydrogen concentration increased with the increase of the PMCR reactor heating temperature. Also, the thermal efficiencies versus the heat supplied have been calculated and the maximum obtained efficiency was 49.32%. Consequently, the evolved hydrogen flow rate appears to depend mainly on the plasma voltage, PMCR reactor heating temperature and the separating temperature of outlet hydrogen and oxygen species. The steam dissociation experiment will be extended to separate hydrogen and oxygen species elements at high temperature conditions. Highlights: Preliminary results of water decomposition using DBD plasma were investigated. The hydrogen mole fraction and mass flow rates increased with the PMCR heating temperature. The maximum conversion rate percent was 42.511%. The maximum energy efficiency was 49.42%.